PENGARUH LATIHAN SENAM KAKI TERHADAP KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS BANGKALA KOTA MAKASSAR - Sri Angriani; Nuraeni Jalil; Baharuddin Baharuddin (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Diabetes mellitus (DM) is a chronic disease indicated by the blood glucose raising above the normal level with the occurrence of large amount of sweet urine. DM treatment normally begins with dietary habit management and physical exercise for two to four weeks. If this treatment does not satisfy the expected target metabolic rate, then it is worthy of pharmacological intervention. One of the physical exercises to do in such condition is a diabetic foot exercise.Diabetic foot exercise is an exercise where feet are moved forward and backward simultaneously or consecutively to strengthen or flex ankles and toes. This exercise can help improve blood circulation and strengthen small muscles on feet area and prevent them from disorder or deformity. This study aimed to describe the effect of diabetic foot exercise on the blood glucose level of type 2 diabetes mellitus patients at Bangkala Health Center, Makassar. It used pre-experimental design with one group pre-test post-test design. Of the total population, 17 samples were chosen using purposive sampling method. The paired t-Test found that diabetic foot exercise has an effect on the blood glucose level on type 2 diabetes mellitus patients at Bangkala Health Center, Makassar where p=0.003 (p<0.005).